The importance of tracking introduced species: nine synonyms of Atheta (Dimetrotina) pasadenae Bernhauer, 1906 (Coleoptera, Staphylinidae, Aleocharinae) - Gusarov, Vladimir I. (Zootaxa, 2016)
Five species names are placed in synonymy with Atheta (Dimetrotina) pasadenae Bernhauer, 1906: Dimetrota vaniuscula Casey, 1911; Atheta pseudocoriaria Bernhauer, 1943 (non Cameron, 1939); A. zealandica Cameron, 1945; A. aucklandensis Pace, 1987 and A. pseudoinsulana Klimaszewski in Klimaszewski et al., 2002. Four names are confirmed to be junior synonyms of A. pasadenae: Atheta pseudolaticollis Erber & Hinterseher, 1992 (non Bernhauer, 1936, non Cameron, 1944); A. immucronata Pace, 1999; A. gulosa Tronquet, 2000 and A. atlantidum Smetana, 2004. Lectotypes are designated for A. pseudocoriaria Bernhauer, 1943; A. zealandica Cameron, 1945 (both designations are to be attributed to Richard A.B. Leschen); and A. pasadenae Bernhauer, 1906. Relationships among the subgenera Xenota Mulsant & Rey, 1874, Dimetrotina Casey, 1911, Oxypodera Bernhauer, 1915 and Mycetota Ádám, 1987 of the genus Atheta Thomson, 1858 are discussed. The name Mycetota Ádám, 1987 is placed in synonymy with Dimetrotina Casey, 1911 (treated as valid subgenus of Atheta), resulting in three new subgeneric assignments: Atheta (Dimetrotina) laticollis (Stephens, 1832), A. (D.) mucronata (Kraatz, 1859), and A. (D.) pasadenae Bernhauer, 1906. Atheta pasadenae is a species with almost cosmopolitan distribution, most likely originating from Africa and (unintentionally) introduced to Europe, North and South America, New Zealand, the Macaronesian islands, Tristan da Cunha archipelago, Juan Fernandez archipelago and Hawaii.